Kazakhstan and USA: on a way of strengthening of the confi dential relations within ensuring nuclear safety (Journal of Philosophy Culture and Political Science, 2019)
The article analyzes the relations between Kazakhstan and the United States in strengthening the trust relationship in the frameworkof Nuclear Safety.